Effect of level of metabolizable energy on the breast and wing weight of local chickens: A meta-analysis - Ramadhani Anisa; Nurgiartiningsih Veronica Margareta Ani; Sjofjan Osfar (BIO Web of Conferences, 2023)
The purposed of this study was to determine the effect of dietary energy and protein balance on the wing weight and breast weight of native chicken using meta-analysis technique. This study used meta-analysis technique to integrate 116 data from 8 articles that contain information about effect of energy and protein balance rations on wings weight and breast weight of local chicken. The meta-analysis technique begins with collecting data from several scientific publications that contain energy and protein levels. The data was tabulated in the form of database with the help of Microsoft excel and in this tabulation process the units of each data were equalized tabulated and analysed using SAS. The results of this study concluded that it took 17.04% of dietary crude protein to produce a minimum breast weight of 151.96grams and 2953.31 kcal/kg to produce 122.66grams of breast weight, as well as 17.43% of raw proteins to make a minimum wing weight of 88.25gram and 2970 kcal / kg to produce an 89.53gram of wing. In conclusion protein requirements and energy metabolism, each pile showed varying results. The existence of this diversity is influenced by genetic and environmental factors.